Embracing hue narratives on colorism and women empowerment through portrait photography - Bianan, Maria Regina G. author; Pueblas, Mishael Jacob L. (2019)
This production thesis, embracing hue, explores the use of portrait photography to depict the diversity of skin color and to present to experiences of young women with regard to skin color discrimination or Colorism. This study is a collection of portraits and personal narratives of 10 young women aged 16-21 years old from Polomolok, South Cotabato, who have been subjected to Colorism but still feel confident in their skin hues. This study offers a glimpse to the real situations of young women in a society dominated by mainstream media, colonial ideals, and big cosmetic companies who impose the ideal beauty standards. With this, embracing hue aims to be an eye-opener for others to recognize the existence and experiences on Colorism of these young women from Polomolok, this study aims to inspire other people to be proud in wearing their skin color. Portrait photography served as an effective communication tool in this study to present colorism and women empowerment to the audience through a public photo exhibit. Through portrait photography, the audience understood the fatal impact of colorism on the well-being of any affected person. At the same time, the audience appreciated the differences of each women in relation to skin color, and they somehow created a sense of association and connection with the subjects? personal experiences.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019